Pandemic Victory Gardens: Potential for local land use policies. (October 2021) - Music, Janet; Finch, Erica; Gone, Pallavi; Toze, Sandra; Charlebois, Sylvain; Mullins, Lisa
Abstract: This viewpoint examines citizen empowerment by gardening in times of crisis, namely, the adoption of the idea of Victory Gardens as a means of resistance to COVID-19. Fear of the collapse of the Canadian food chain supply at the beginning of the pandemic led to an increase in urban gardening. The government-created Victory Garden program of the Second World War urged citizens to contribute to the war effort by growing their own food. Social media use of hashtags associated with victory gardening are shown as citizen engagement or intent to engage with local gardening programs and home food production. While a scaled-down victory garden-like program might see a resurgence in urban geographies, if local planning policies and government-led community gardening efforts supported growth in this area. Highlights: Fear of food shortages led to panic buying and stockpiling during the COVID-19 pandemic. People announced growing Victory Gardens on social media as a form of empowerment. Local governments have an opportunity to increase citizen engagement. Governments can strengthen local food supply chains through land use policies that allow for growing food.